Tracking development assistance for health and for COVID-19: a review of development assistance, government, out-of-pocket, and other private spending on health for 204 countries and territories, 1990–2050. Issue 10308 (9th October 2021) - ,; Micah, Angela E; Cogswell, Ian E; Cunningham, Brandon; Ezoe, Satoshi; Harle, Anton C; Maddison, Emilie R; McCracken, Darrah; Nomura, Shuhei; Simpson, Kyle E; Stutzman, Hayley N; Tsakalos, Golsum; et al.
Summary: Background: The rapid spread of COVID-19 renewed the focus on how health systems across the globe are financed, especially during public health emergencies. Development assistance is an important source of health financing in many low-income countries, yet little is known about how much of this funding was disbursed for COVID-19. We aimed to put development assistance for health for COVID-19 in the context of broader trends in global health financing, and to estimate total health spending from 1995 to 2050 and development assistance for COVID-19 in 2020. Methods: We estimated domestic health spending and development assistance for health to generate total health-sector spending estimates for 204 countries and territories. We leveraged data from the WHO Global Health Expenditure Database to produce estimates of domestic health spending. To generate estimates for development assistance for health, we relied on project-level disbursement data from the major international development agencies' online databases and annual financial statements and reports for information on income sources. To adjust our estimates for 2020 to include disbursements related to COVID-19, we extracted project data on commitments and disbursements from a broader set of databases (because not all of the data sources used to estimate the historical series extend to 2020), including the UN Office of Humanitarian Assistance Financial Tracking Service and the International Aid Transparency Initiative. We reported all the historic and future spending estimates in inflation-adjusted 2020 US, 2020 US per capita, purchasing-power parity-adjusted US per capita, and as a proportion of gross domestic product. We used various models to generate future health spending to 2050. Findings: In 2019, health spending globally reached 8·8 trillion (95% uncertainty interval [UI] 8·7–8·8) or 1132 (1119–1143) per person. Spending on health varied within and across income groups and geographical regions. Of this total, 40·4 billion (0·5%, 95% UI 0·5–0·5) was development assistance for health provided to low-income and middle-income countries, which made up 24·6% (UI 24·0–25·1) of total spending in low-income countries. We estimate that 54·8 billion in development assistance for health was disbursed in 2020. Of this, 13·7 billion was targeted toward the COVID-19 health response. 12·3 billion was newly committed and 1·4 billion was repurposed from existing health projects. 3·1 billion (22·4%) of the funds focused on country-level coordination and 2·4 billion (17·9%) was for supply chain and logistics. Only 714·4 million (7·7%) of COVID-19 development assistance for health went to Latin America, despite this region reporting 34·3% of total recorded COVID-19 deaths in low-income or middle-income countries in 2020. Spending on health is expected to rise to 1519 (1448–1591) per person in 2050, although spending across countries is expected to remain varied. Interpretation: Global health spending is expected to continue to grow, but remain unequally distributed between countries. We estimate that development organisations substantially increased the amount of development assistance for health provided in 2020. Continued efforts are needed to raise sufficient resources to mitigate the pandemic for the most vulnerable, and to help curtail the pandemic for all. Funding: Bill & Melinda Gates Foundation.